Embedded image capture system for smart camera application - Mahzan Musa (Universiti Malaysia Perlis, 2008)
The name of this project is a Embedded Image Capture System for Smart Camera Application. This project involved the software development and also hardware development. The embedded image capture system will been develop using Linux operation using C language programming. The operating system that will be chosen is TS-Linux that operated in the Single Board Computer (SBC). The will have two phase for this project. The first phase is developing the software part and hardware part at the desktop PC or laptop. The second phase is to transfer all the software part and hardware to the SBC. The project will start with the software part. In this part, the Linux embedded system will be design and make interfacing with the hardware part. The hardware part that will be use in this project is webcam camera via Universal Serial Bus (USB). A smart camera combines image sensing, image processing and communication within a single device. This project implementation of a smart camera for surveillance system that can interpret images such as object like vehicle, animal, human and this and the ability to identify images and react with specific tasks such as alarm trigger and notify danger.